(untitled) (Research, Society and Development, 2021)
The aging process occurs naturally, it does not depend on the individual’s will, presenting constant processes of modifications, where multiple transformations occur, and they are irreversible despite the advancement of medicine. It is heterogeneous and individual, as each person has their own speed to age, it is harmful, harmful, as it leads to a progressive loss of functions. The present study aims to discuss the relationship of the elderly with the family and society, addressing who is responsible for the care and preservation of the rights of the elderly. It is a narrative review, with a qualitative exploratory approach at the bibliographic level, through electronic search in Scielo; Academic Google; Lilacs; books; sites based on keywords: Aging, the elderly ’s relationship with family and society. As results obtained, several publications show that the family, in most cases, develops negative feelings regarding the care for the elderly, seeing it as an obstacle that hinders the “normal” development of daily activities. On the other hand, for most elderly people, the family has an essential role in maintaining their survival. These facts permeate society, which is unprepared to develop resolutive assistance in this area. From this bibliographic review, there is then a need to establish more effective and dynamic assistance schemes, capable of assisting the growing demands of the elderly and their families, who in many cases experience problems not always known by the health teams.